Adecuación de material didáctico con instrumentos musicales para desarrollar el lenguaje musical en la población infantil de la sala de estimulación temprana de la carrera de parvularia de la U.T.C periodo 2011-2012 - Rodriguez Vizuete, Catalina Maribel (2012)
The following research was based on the urgent creation of a stimulation room to meet needs in the pediatric population. It was created at the Technical University of Cotopaxi. In order to stimulate the infant different characteristics such as language development by musical instruments. For the collection of information was considered surveys and interviews. These techniques determined that there is a high incidence of children with language problems. For this reason, the proposal was based on the importance of music on power, the same that goes further than words. The pleasure of sharing. The music builds connections between parents and children. As the sounds and rhythms surround the children in a world of sensations and feelings.